Changes in Cortisol Levels before and after Supportive Psychotherapy in Patients with Comorbid Cervical Cancer Distress with Depression Type: Perubahan Kadar Kortisol sebelum dan sesudah Psikoterapi Suportif pada Pasien Kanker Serviks dengan Komorbiditas Distres Tipe Depresi - Laila Nuranna; Kartiwa H Nuryanto; Andriansyah Andriansyah; Sylvia D Elvira; Bambang Sutrisna (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To prove the success of supportive psychotherapy thatwas provided as a distress therapy on advanced cervical cancer.Knowing the prevalence of distress type of depression in patientwith epithelial cervical cancer, proving the benefits of psychotherapysupportive for distress can decreasing cortisol level in cervicalcancer patient, can assess distress thermometer score, HAM-D17score and scoring incident predictors of distress with depressiontype.Methods: There were 32 subjects from 71 advanced cervical cancerpatients had mild-moderate depression. Then randomizationblocking was performed to determine a subject who entered thetreatment group (n = 16) who got supportive psychotherapy orcontrol group who got common psychotherapy (n = 16). All ofparticipants assessed the distress level with cortisol value, distressthermometer score, and HAM-D17 score before and after they gotsupportive psychotherapy.Results: After the intervention of psychotherapy in the treatmentgroup decreased HAM-D17 score, the average decline 7.53 (SB 3.34).The mean decreasing in the control group was 3.98 (SB 2.85). Thereis a significant difference in mean reduction in HAM-D17 scores ontreatment and control groups with p = 0.003 (p <0.005). There wasdecreasing blood cortisol level in the treatment group amounted to39.43, while the control group there was a drop of 1.59. The reductionof cortisol level in the treatment group and the control has a pvalue0.302. After got supportive psychotherapy, found a decreasingthe average value of the thermometer distress in the treatmentgroup 3.02 and the control group 2.51, with a p value more than0.492.Conclusion: There were 45% of cervical cancer patients in the clinicexperiencing distress disorder with depressive type. The bloodcortisol level could be decreased by giving supportive psychotherapywith a mean decrease of 39.43 nmol/l. There was a significantreduction in the level of depression (HAM-D17 score) of 7.53 pointsand distress thermometer impairment by 3 points after givensupportive psychotherapy. Obtained scoring predictors for theoccurrence of distress type of depression in patients with advancedcervical cancer with a sensitivity of 46.15% and a specificity of89.47%.[Indones J Obstet Gynecol 2018; 6-3: 179-187]Keywords: cervical cancer, cortisol, distress, distress thermometer,HAM-D17 score